The man who loved seagulls : essential life lessons from the world's greatest wisdom traditions - Osho. (b)
Discusses essential stories and parables from the world's great wisdom traditions of Zen, Taoism, Christianity, and Judaism. This book presents a collection of stories which have been interpreted and applied to the concerns of modern day life. It includes such topics as the futility of chasing happiness, and the journey from fear to freedom.
Keywords: Spirituality